Ideational leadership in German welfare state reform : how politicians and policy ideas transform resilient institutions - Stiller, Sabina (Changing welfare states., 2010)
The author of this study argues that key politicians and their policy ideas, through "ideational leadership", have played an important role in the passing of structural reforms in the change-resistant German welfare state